Type III Sturge Weber Syndrome, An Uncommon Cause of Status Epilepticus - Coronado-Lopez, Juan Pablo; Coronado, Juan Felipe; Gomez-Urrego, Jose Fernando; Londono-Chavez, Richard (Journal of Pediatric Epilepsy, 2022)
Introduction Sturge Weber syndrome (SWS) is a rare neurocutaneous condition due to the mutation of the GNAQ gen. This condition is characterized by skin, eye, and brain compromise, but the type III only affects the brain, making it a challenging condition to diagnose.Clinical Case A Hispanic 4 year-old female, with a history of complex febrile seizure in her medical records, presented to the emergency room in status epilepticus after 24 hours of upper respiratory symptoms. After a neurological and radiologic evaluation, SWS III was diagnosed, which led to a pharmacological adjustment for achieving control of the seizures, with a great clinical evolution.Discussion The pathophysiology, diagnostics, and proper management of this disease are discussed.Conclusion SWS is a rare neurocutaneous disease, usually diagnosed in patients with pathognomonic features, however it is important to know that type III SWS exists and represents a challenging diagnosis, leading to a time-race for starting proper management, considering that the outcome includes a better life-quality, a higher cognitive result, and reduced morbimortality.
Keywords: Sturge-Weber syndrome; febrile seizure; neurosurgery